Transformasi Digital: Inovasi untuk Pendidikan Berkelanjutan - Suryaningrat Suryaningrat; Muhamad Alfiansyah; Dea Khoirunnisa; Elin Nurjanah; Gina Suraya (Journal on Education, 2025)
Digital transformation plays an important role in advancing the world of education in Indonesia, in the transformation has emerged various impacts in teaching and learning activities on students and teachers. In this journal, we will outline some of the materials that explain the important role of digital transformation such as digital literacy that can provide access to increased information, skills needed in the current era. Then in addition to evolving learning, there is also a need for evolution in digital assessment that aims to assess the progress of students. While digital transformation provides many opportunities for educational advancement, there are hurdles that require cohesiveness among users and a better experience. Therefore, in order to obtain credible data, we analyzed various scholarly works relevant to this issue.